Capacity Assessment of Community Clinic (CC) as an Information and Support Hub during Future Outbreaks: Lessons Learnt from the COVID-19 Outbreak - Samm A, Anika; Kamal, A S M Maksud; Hossain, Abrar; Hossain, Md Motahar; Hassan, SM Kamrul; Jahan, Hasina; Hayat, Tanzim; Jui, Tasnim Jabin; Sifa, Shamima Ferdousi; Awal, A S Nurullah (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
The study delves into the potential of Community Clinics (CCs) in Bangladesh to function as crucial information and support hubs during pandemics and outbreaks. By examining both internal and external factors, including organizational structure, roles, responsibilities, infrastructure, skills, tools, existing organogram, government policies, and community clinic dynamics, the research assesses the capability of CCs in this role. Through a telephonic survey of 100 Community Health Care Providers (CHCP) and Key Informant Interviews (KII) with Community Based Health Care (CBHC) officials, valuable insights were gained. While the findings reveal that CCs may not be comprehensive treatment centers for pandemics, they can effectively serve as information and support hubs, aligning with their mandates. To enhance their efficiency in this role, upgrading the WASH sensitivity of CCs is recommended, along with other measures to improve their capacity during disease outbreaks. The study underscores the significance of recognizing CCs as vital assets in combating emerging health hazards, and strategic improvements can further strengthen their contributions in addressing public health challenges. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(1), 2023, P 41-56